Synthesis of 2H-Thiopyrans via Multicomponent Reactions in Water - Rostami-Charati, Faramarz (Synlett, 2013)
A series of 2H-thiopyran derivatives has been synthesized via one-pot multicomponent reactions of dialkyl acetylenedicarboxylates, arylisothiocyanates, and α-bromoketones in the presence of triphenylphosphine in water under both conventional heating and microwave irradiation. The yields obtained under microwave irradiation were superior and the reaction times were reduced in comparison with conventional heating.
Keywords: 2H-thiopyran; triphenylphosphine; α-bromoketone; microwave irradiation; arylisothiocyanate